Global Marketing: Emerging Market Economies' Challenges, Opportunities and Effective Marketing Strategy for Success - Chea, Ashford C. (Business and Economic Research, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The paper's purpose has been to conduct a rigorous literature review and analyze emerging market economies' competitive marketing environment. First, the article presents the theoretical foundation that underpins global firms' decisions to expand in emerging markets. Second, the paper thoroughly reviews the academic literature on emerging market research. Third, the unique characteristics of emerging markets are analyzed. Fourth, the article explores the influence of culture on consumer behavior, decision processes, and global branding in emerging markets. The paper outlines effective market segmentation and marketing mix strategies in emerging markets. The article ends with significant research findings, marketing implications, and recommendations for global corporations and their marketing managers.